Acute effects of ballistic versus heavy-resistance exercises on countermovement jump and rear-hand straight punch performance in amateur boxers - Yi, W.; Chen, C.; Zhou, Z.; Cui, W.; Wang, D. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Ballistic and heavy-resistance exercises may potentially enhance lower body power, which is paramount for the punching performance of amateur boxers. This study aimed to determine the acute effects of ballistic exercise (BE) and heavy-resistance exercise (HRE) on countermovement jump (CMJ) and rear-hand straight punch performance in amateur boxers.